2010
DOI: 10.1002/jqs.1399
|View full text |Cite
|
Sign up to set email alerts
|

Chironomid‐inferred late‐glacial summer air temperatures from Lough Nadourcan, Co. Donegal, Ireland

Abstract: Western Ireland, located adjacent to the North Atlantic, and with a strongly oceanic climate, is potentially sensitive to rapid and extreme climate change. We present the first highresolution chironomid-inferred mean July temperature reconstruction for Ireland, spanning the lateglacial and early Holocene (LGIT, 15-10 ka BP). The reconstruction suggests an initial rapid warming followed by a short cool phase early in the interstadial. During the interstadial there are oscillations in the inferred temperatures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 50 publications
4
43
0
1
Order By: Relevance
“…The RMSEP of 0.57°C is considerably smaller than error from other regional training sets, lending this model greater applicability for reconstructing Ireland's relatively modest Holocene temperature fluctuations (Swindles et al 2013). Past chironomid-based temperature reconstructions in Ireland have applied transfer functions from northern Europe to study large temperature fluctuations during the Pleistocene-Holocene transition (Watson et al 2010;van Asch et al 2012). This was necessary as models with large ranges are required to reconstruct these extreme events.…”
Section: Inference Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…The RMSEP of 0.57°C is considerably smaller than error from other regional training sets, lending this model greater applicability for reconstructing Ireland's relatively modest Holocene temperature fluctuations (Swindles et al 2013). Past chironomid-based temperature reconstructions in Ireland have applied transfer functions from northern Europe to study large temperature fluctuations during the Pleistocene-Holocene transition (Watson et al 2010;van Asch et al 2012). This was necessary as models with large ranges are required to reconstruct these extreme events.…”
Section: Inference Modelmentioning
confidence: 97%
“…Two recent chironomidbased quantitative temperature reconstructions of the Pleistocene-Holocene transition in western Ireland (Watson et al 2010;van Asch et al 2012) used training sets based largely on lakes from Norway and Svalbard (Brooks and Birks 2001) and Norway and the Alpine region (Heiri et al 2011). Although training sets from different regions have been successfully applied to sites in Ireland and the United Kingdom (Langdon et al 2004), regional differences in lake characteristics (Gandouin and Franquet 2002), historical human impacts (Bitusik and Svitok 2006) and local patterns in chironomid distribution (Murray and O'Connor 1992) may affect the applicability of inference models among different regions.…”
Section: Introductionmentioning
confidence: 99%
“…3c and (2) those species previously reported as warm or cold stenotherms. On the left side of the diagram, Polypedilum nubifer-type, Dicrotendipes nervosus-type and Tanytarsus mendax-type have been previously reported as warm stenotherms (Watson et al, 2010;Brooks and Heiri, 2013), and were defined as thermophilous taxa here. Procladius choreus-type and Microchironomus were eliminated because their high scores on the positive axis may be because in the Gonghai Lake region they are indicators of deep water (Wang et al, 2016).…”
Section: Modern Chironomid Assemblagesmentioning
confidence: 99%
“…Although this data set suggested that chironomid assemblages in the region responded significantly to fluctuations in water depth since the last deglaciation (Wang et al, 2016), the existence of several typical stenothermal species (e.g. Hydrobaenus conformis-type, Dicrotendipes nervosus-type) in the fossil sequence (Wang et al, 2016), which are sensitive to temperature variability on various timescales (Cranston et al, 1983;Brodin, 1986;Watson et al, 2010;Brooks and Heiri, 2013), offers great potential for paleotemperature reconstruction in the area. In addition, as well as having significant regional environmental effects, past climate change may also have triggered human societal crises .…”
Section: Introductionmentioning
confidence: 97%
“…In Ireland, chironomid research is largely restricted to temperature reconstructions over the late Glacial to early Holocene transition (Watson et al, 2010;van Asch et al, 2012) using training sets from Scandinavia and the Alpine region, and more qualitative archaeology-based studies during the Holocene (Ruiz et al, 2006;Taylor et al, 2013). Climate change in Ireland over this time remains poorly understood as the palaeoclimate record for the island is marked with ambiguity, largely due to proxy complexities, subdued temperature ranges and a prominent human influence since the mid-Holocene.…”
Section: Introductionmentioning
confidence: 98%